2020
DOI: 10.3390/md18100508
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry, Biochemistry and Pharmacology of Marine Natural Products from Leptolyngbya, a Chemically Endowed Genus of Cyanobacteria

Abstract: Leptolyngbya, a well-known genus of cyanobacteria, is found in various ecological habitats including marine, fresh water, swamps, and rice fields. Species of this genus are associated with many ecological phenomena such as nitrogen fixation, primary productivity through photosynthesis and algal blooms. As a result, there have been a number of investigations of the ecology, natural product chemistry, and biological characteristics of members of this genus. In general, the secondary metabolites of cyanobacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Leptolyngbya had no genus specific metabolites annotated in the GNPS database. While there are several metabolites known to be produced by Leptolyngbya [ 36 ], only six of them are present in the GNPS database (dolastatin 12 [ 37 ], palmyrolide A [ 38 ], phormidolide [ 39 ], scytonemin [ 40 ], shinorine [ 41 ] and stilbene [ 42 ]), and these were not detected in our analyses. Spirulina and Oscillatoria were not sampled for LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptolyngbya had no genus specific metabolites annotated in the GNPS database. While there are several metabolites known to be produced by Leptolyngbya [ 36 ], only six of them are present in the GNPS database (dolastatin 12 [ 37 ], palmyrolide A [ 38 ], phormidolide [ 39 ], scytonemin [ 40 ], shinorine [ 41 ] and stilbene [ 42 ]), and these were not detected in our analyses. Spirulina and Oscillatoria were not sampled for LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with our previous reports that the genus Moorea (renamed to Moorena ) is distinctive from other cyanobacteria, especially regarding its natural product potential [ 7 ]. Other genera included in this study, such as Okeania , Leptolyngbya and Oscillatoria , have also been reported as abundant producers of natural products [ 36 , 43 ]. This contrasts with the genus Spirulina which is not reported as a prolific metabolite producer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the higher abundance of Ascomycota is associated with their important role in ecosystem succession ( 48 ). Dominance among taxa unique for tributaries in bacterial community was led by widespread forest soil bacteria from families Chitinophagaceae and Saprospiraceae ( 49 ) and Leptolyngbyaceae , which among other functions have the function of nitrogen fixation ( 50 ). Among rare taxa, bacteria from families associated with aromatic decomposition can be found, for instance Pelotomaculaceae ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…SM1A02, which is a type of anammox bacterium ( Ding et al, 2018 ), also showed significant negative correlations with both TN and NH 4 + in Lake Dongqian. Leptolyngbya , which is a well-known genus of Cyanobacteria associated with nitrogen fixation, primary productivity, and algal blooms ( Li et al, 2020 ), was significantly and positively correlated with Temp, TN and NH 4 + in Lake Dongqian. Therefore, we suggest that most of the keystone taxa can be used as bio-indicators to assess the water quality together with the abiotic indicators in Lake Dongqian since they were significantly related to a number of water variables and played key ecological functions.…”
Section: Discussionmentioning
confidence: 99%